Universities, SMEs and social capital: Can you get too much of a good thing? An illustrative analysis of one university's knowledge exchange programme. (December 2016) - Gordon, Ian
This article explores a university knowledge exchange programme for small and medium-sized enterprise (SME) owner-managers. Specifically, it considers why a programme designed to achieve growth in a group of SMEs through the creation of a network high in social capital may have become a constraint on the programme's effectiveness over a period of 5 years. The article presents findings from ethnographic observation and interviews with eight participants. The main findings suggest that university facilitators should guard against becoming part of a strong tie network of delegates, which in this case may have resulted in a reduction in their ability to bridge to other groups and networks. In addition, without the periodical introduction of new activities, there is the danger that the group will become stale.